(untitled) (CIPEEX, 2025)
Introduction: Chronic kidney disease (CKD) affects 8–16% of the adult population and is primarily treated with dialysis and transplantation, both of which have limitations. Advances in Tissue Engineering and Regenerative Medicine suggest the use of decellularized extracellular matrix (ECM) for renal regeneration. Objectives: To review the literature on renal hydrogels based on decellularized ECM, emphasizing their clinical applications and emerging challenges. Methodology: A literature review was conducted in PubMed (2015–2024), including peer-reviewed studies on renal hydrogels derived from decellularized ECM. Results: Six main studies were analyzed. Quinteira et al. (2024) developed porcine tissue renal hydrogels with therapeutic potential. Hiraki et al. (2018) replicated the renal microenvironment, preserving ECM proteins. Soranno et al. (2023) demonstrated improved renal function using injectable hydrogels. Guan et al. (2015) preserved renal vasculature but observed thrombosis after two weeks. Caralt et al. (2015) identified the Triton X-100/SDS protocol as the most effective for decellularization. Remuzzi et al. (2017) reported difficulties in cell distribution and viability. Conclusion: Decellularization and recellularization of renal ECM have shown significant advances, particularly with the Triton X-100/SDS protocol. However, challenges such as thrombosis and limited cell distribution must be overcome to enable the clinical application of renal hydrogels.